Un modelo para diseñar aprendizajes mediante proyectos multidisciplinares - Sílvia Espinosa-Mirabet; Marianna Soler i Ortega; Maria Lluïsa Escoda; Jaume Puig-Bargués; Inés Ferrer Real (Universitat Politècnica de València, 2015)